Review: Muhammadiyah's Views and Perspectives on the Rise of Halal-Labeled Cosmetics and Health Products in Indonesia - Hakim, M Arif Lukman; Sofiana, Nurani; Firdaus, Stradivary Maulida (Civiliza Publishing, 2024)
The growth and importance of halal products is of particular importance in the cosmetics and healthcare sector in Indonesia, which has the largest Muslim population in the world. With the increasing public awareness of safe and religiously-compliant products, the demand for halal products continues to rise. The concept of halal, which means “permissible” in Islam, covers not only food but also cosmetics and medicines, where halalness is determined by the ingredients, production process, as well as certification from relevant institutions. This research uses the literature study method to explore Muhammadiyah's views on this phenomenon. The results show that halal cosmetics not only fulfill aesthetic aspects but also reflect religious values. Halal certification is important to provide assurance to consumers that the product is safe and in accordance with Islamic law. In addition, the global halal industry is showing significant growth, with various certification bodies around the world ensuring product quality and compliance with sharia principles. This research confirms that halal is not just a label, but an integral part of a Muslim's obedience in choosing products.